Anterior Shoulder Stabilization Using a Single Portal Technique With Suture Lasso - Elena, Nicholas (Arthrosc Tech, 2018)
Open Bankart repair was the standard technique used in the past, but the request for less invasiveness, always pursued by every surgeon, pushed the development of the arthroscopic procedure. Nowadays the stabilization of the anteroinferior labrum is usually performed with an arthroscopic technique that uses the classic posterior portal and 2 anterior working portals. Because arthroscopy is progressing steadily under every aspect, there is now the chance to use only one working portal with the aid of a suture passer. One less portal not only means less invasiveness but also less postoperative pain and possible shorter operative time. This Technical Note is focalized in the description of a Bankart repair technique with a single working portal and the aid of a suture lasso.